PERAN PEMERINTAH DAERAH DALAM RESOLUSI KONFLIK ANTARA PT. TASMA PUJA DI DESA KEPAYANG SARI DAN MASYARAKAT DESA ALIM KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Setiawan, Diki Aries; ,, Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study discusses the existence of approximately 91 HA of 110 HA of land located in the Alim Village area, Batang Cenaku District, Inhu Regency, Riau Province. The land was seized by PT Tasma Puja and is located in Kepayang Sari Village, Batang Cenaku District. The government did not immediately determine the boundary between Kepayang Sari Village and Alim Village. The government's efforts to mediate the conflict have not been successful so far and NGOs and Alim Village feel that the local government is siding with PT Tasma Puja, resulting in violence and threats of land occupation by the community. This study uses conflict management theory (Hidayat, 2016) which is conflict management using a series of techniques or certain steps by a third party or conflicting parties in an effort to minimize the negative impact of conflict and direct destructive conflict into a constructive conflict that benefits all parties. The type of data in writing this thesis is descriptive qualitative where this study explores and analyzes to provide meaning and significance in solving problems. The conclusion of this study is that efforts made to resolve land conflicts in Kepayang Sari Village and Alim Village, Batanag Cenaku District, Indragiri Hulu Regency are meetings at the Kepayang Sari Village office, both from the company PT. Tasma Puja and the community to find the best solution. Keywords: Role of Local Government, Conflict Resolution, PT. Tasma Puja, Aim Village, Kepayang